Synthesis and characterization of a narrow size distribution nano phase change material emulsion for thermal energy storage. (1st May 2017) - Zhang, G.H.; Zhao, C.Y.
Highlights: A series of novel nano-PCM emulsions were successfully synthesized. Nano-PCM emulsions can be synthesized in a cost-effective form. Prepared nano-PCM emulsions presented good thermo-physical properties. Prepared nano-PCM emulsions were extremely stable. Prepared nano-PCM emulsions can be utilised as potential heat transfer fluid and energy storage media. Abstract: This paper introduces a novel nano phase change material emulsion (NPCE) which was synthesized by direct miniemulsion method. A series of NPCEs using n -octadecane as phase change material were prepared with 10 wt.%, 20 wt.%, 30 wt.% and 40 wt.%, respectively. Prepared NPCEs were characterized by particle size analyzer, transmission electron microscopy (TEM), differential scanning calorimeter (DSC), thermal conductivity meter and rheometer. The TEM image shows that all the NPCEs are successfully synthesized with well dispersed nanoparticles. The DSC results indicate that the melting behaviour of n -octadecane is close to NPCEs and the supercooling is observed in all the NPCEs. Particle size and rheological analyses demonstrate that prepared NPCEs present a narrow size distribution and an extreme stable form. In comparison with the conventional phase change material slurry (PCS) and microencapsulated phase change material slurry (MPCS), the NPCE tends to be much more stable and importantly it can be synthesized in a cost-effective form in terms of method and materials.